Solar Still: Water for the Future - Siti Nudra Shafinie, Ab Aziz; El Hadad, Omar; Syarifah, Abd Rahim; Chew, Few Ne (Asian Research Publishing Network (ARPN), 2016)
Being an abundant natural resource that covers three quarters of the earth’s surface, water still a major issue, as less than 1% of fresh water is actually within human reach. Solar energy, most recommended renewable energy source is widely used in desalination fields. Solar distillation, particularly solar still is expected to solve this fresh water production problem without causing any fossil energy depletion, hydrocarbon ollution and environmental degradation. However, the efficiency of the solar still is debatable. As the main reason of low productivity in a solar still is the low heat transfer inside the unit itself therefore, a thoroughly modification on solar still design is presented based on the scope of increasing the heat transfer process inside the unit. Significantly, ntroducing optical controlling techniques together with focused sunlight receiver and having the process to operate under low pressure have speed up the rate of production within 10 hours of day light. However, the presence of focused sunlight receiver is not seem to improve the production of the solar still yet an increase value is recorded.